The impact of the Kamp model on the acquisition of historical concepts and the retention of the history material for fourth grade students (literary) - مولود توفيق, بشائر (Al-Adab Journal, 2018)
University of Baghdad - Center for Educational and Psychological ResearchChapter I : The increasing number of complaints from the many events and years and the rigidity of history, the difficulty of understanding and assimilation, and the huge amount of information and the most prominent educators in the use of teachers to the traditional way of teaching history, which is based on the preservation and information and facts without linking them, which called for the idea of ​​using concepts as elements of the organization of curricula .The importance of research and the need for it The models were designed to provide the learner with educational experiences that fit the presentation of logical information to the learner and the variety of instructional models. Their importance lies in providing learners with basic pillars for the development of thinking methods. Gerold Kemp's model is based on the interrelationship between its parts and components. It follows systematic and interrelated steps in teaching. The teacher avoids chaos and randomness, and prompts the student to actively and dynamically engage in learning to acquire what is presented E teacher of informationResearch Objective: The current research aims to identify: The impact of the Kamp model on the acquisition of historical concepts and the retention of the history material for fourth grade students (literary) Search limits: Current search is limited to- Fourth grade students- Book of the history of Islamic civilization scheduled for the fourth grade preparatory (literary)Chapter II Arabic studies and foreign studies Studies on the CAMP model in collection and retention. Chapter III Experimental Design: The researcher adopted experimental design with two experimental groups and a control group The researcher rewarded (test previous knowledge, IQ test scores) Research tools Prepare a test for collection after the statistical procedures in terms of difficulty and discrimination and after completing the requirements of the experiment, and applied the post-test in the acquisition of historical concepts and thus ended the research experience and after (21) days, the researcher re-testing of the acquisition of concepts to identify the retention of material.Chapter Four: The researcher presented in this chapter the results reached according to the objective of the research and hypotheses rejected the hypothesis of research and the results showed that there are differences of statistical significance between the grades of students of the experimental group and the control group.